Implementation of Problem Based Learning (PBL) Learning Model on Literacy Ability - Nurhayati, Nunung (UNIB Press, 2023)
Currently, education in Indonesia has a relatively low ranking compared to other countries in terms of the education system. There are several reasons why education in Indonesia is still low compared to other countries. One of them is the influence of a lack of literacy or interest in reading on students. The purpose of this study is to describe the results of research on the implementation of the Based Learning model on literacy skills. These findings are then used as a basis for looking for new ways, especially the benefits of the PBL model in increasing basic education literacy skills. The research method uses content analysis of the 2018-2022 articles from Google Schoolar, Scopus.com and Garuda websites which are searched using the keyword